Noken dan korupsi: Degradasi nilai budaya antikorupsi pada era otonomi khusus di Papua - Bonefasius Bao; PRT. Paramma; Anitha Nurak; Hendrik Vallen Ayomi (Integritas: Jurnal Antikorupsi, 2023)
In the past, Indigenous Papuans had a unique way of teaching their cultural values of hard work, honesty, openness, and authority. These values are contained in the Noken. Noken is a handicraft product made from natural materials which has the same function as a bag. It is used to fill crops, groceries, and personal items and is used in ceremonies as a souvenir and an accessory for women. The philosophy of the Noken is full of values, including transparency and integrity, wherein Papuans were taught an anti-corruption culture from their early life. This contradicts the current situation, where corruption practices are increasing, especially among public officeholders. This study aims to analyse the degradation of Papua’s anti-corruption culture after the implementation of special autonomy by using a qualitative perspective, namely gathering information from selected informants through focus group discussions and in-depth interviews. The results of this study indicate that the causes of the degradation of the anti-corruption culture are due to changes in consumptive lifestyles and weak supervision, a high-cost political system, and convoluted bureaucratic flows. The consequence of this degradation is the fading of Noken-based anti-corruption culture, dependence on special autonomy funds, and the sharpening of social conflicts. For this reason, political action and goodwill from stakeholders are needed to revitalise Noken's noble values through internalising said values in social life.